Epigallocatechin-3-Gallate As A Potential Modulator of Tgf- Β And Tnf- Α Expression In Human Pterygium Fibroblasts: A Literature Review - Kartika Anggraeni, Maharani; Komaratih, Evelyn; Firmansjah, Muhammad; Sasono, Wimbo; Indriaswati, Luki; Parma Jaya, Ratna; Agus Purwanto, Djoko (Journal of Neonatal Surgery, 2025)
Pterygium is a chronic ocular surface disorder characterized by fibrovascular proliferation, often resulting in visual impairment and high recurrence rates after treatment. Fibrosis and inflammation are key pathological processes, with Transforming Growth Factor Beta (TGF-β) and Tumor Necrosis Factor Alpha (TNF-α) playing central roles. This literature review aims to explore the potential of Epigallocatechin-3-gallate (EGCG) in modulating the expression of TGF-β and TNF-α in human pterygium fibroblasts, and to evaluate its efficacy as an anti-inflammatory and antifibrotic agent in pterygium management. A comprehensive review of relevant in vitro and experimental studies was conducted, focusing on the biological effects of EGCG on pterygium fibroblast behavior, including proliferation, migration, cytokine expression, and apoptosis, particularly through TGF-β and TNF-α signaling pathways. EGCG has been shown to significantly reduce the expression of TGF-β and TNF-α, inhibit fibroblast proliferation and migration, and promote apoptosis in pterygium fibroblasts. Its mechanisms involve modulation of fibrotic and inflammatory signaling pathways. EGCG demonstrates promising therapeutic potential as an adjuvant agent in the treatment of pterygium. Its ability to target both inflammation and fibrosis suggests a role in reducing recurrence rates and improving treatment outcomes. Further studies are needed to support its clinical application.